A case study – The Occurrence of pests in stands of newly introduced energy crops in large-scale Pilot experiments in conditions of Central Europe - Tóth Štefan; Tancik Ján; Šoltysová Božena; Porvaz Pavol (Agriculture, 2023)
The objective of this paper is to document the occurrence of pests recorded in a large-scale pilot field experiment, where a unique set of newly-introduced herbaceous energy crops was tested under conditions of eastern Slovakia. The set consisted of Elymus elongatus, Secale cereanum, Silphium perfoliatum, Galega orientalis, Sida hermaphrodita, Panicum virgatum, Amaranthus spp., Panicum miliaceum, Sorghum sudanense, and Sorghum bicolor. A total of 14 cultivars were tested on 4 sites during 4 crop years (2016 – 2020). At least 17 species of pests were recorded in total, as some of the species may represent the identity of the couple or several relative ones, which was rare only as usually a fower common species. The occurred pests list consists of Anisoplia lata Erichson, Agriotes lineatus L., Capreolus capreolus L., Deroceras agreste L., Oulema gallaeciana Heyden, Lepisma saccharinum L., Lepus europaeus Pallas, Meloe proscarabaeus L., Metcalfa pruinosa Say, Microtus arvalis Pallas, Philaenus spumarius L., Psylliodes chrysocephala L., Rhopalosiphum padi L., stemborers as any insect larva or arthropod boring into plant stem, Sus scrofa L., Aleyrodes proletella L., Tettigonia viridissima L., and Trialeurodes vaporariorum Westwood. Overall, the occurrence of pests was regular and scattered, and damages caused by them were negligible usually, but a total destruction of the crop stand even cultivar-specific was recorded too. Most of the meaningful pests are primarily field hunting animals and only secondarily commonly occurring insect species, which for further observations are desirable in order to capture the tendency of important pests’ overpopulation, confirming respectively. Although even rare finding of the single caterpillar of Xylena exsoleta exsoleta L. was recorded in a buffer zone, within the experiment no newly introduced pest species was recorded.